'In my life antidepressants have been…': a qualitative analysis of users' diverse experiences with antidepressants. Issue 1 (December 2016) - Gibson, Kerry; Cartwright, Claire; Read, John
Abstract Background While mental health professionals have focused on concerns about whether antidepressants work on a neurochemical level it is important to understand the meaning this medication holds in the lives of people who use it. This study explores diversity in the experience of antidepressant users. Methods One thousand seven hundred forty-seven New Zealand antidepressant users responded to an open-ended question about their experience of antidepressants. This was analysed using content and thematic analysis. Results There was considerable diversity in participants' responses including positive (54 %), negative (16 %) and mixed (28 %) experiences with antidepressants. Those with positive experiences saw antidepressants as a necessary treatment for a 'disease', a life saver, a way of meeting social obligations, dealing with difficult circumstances or a stepping stone to further help. Negative themes described antidepressants as being ineffective, having unbearable side effects, undermining emotional authenticity, masking real problems and reducing the experience of control. Mixed experience themes showed how participants weighed up the unpleasant side effects against the benefits, felt calmer but less like themselves, struggled to find the one or dosage and felt stuck with continuing on antidepressants when they wished to stop. Conclusions Mental health professions need to recognize that antidepressants are not a 'one size fits all' solution.